The systematic biases in decision-making in the mutual-fund markets: Market states and disposition effect - Shih-Wei Wu; Juli Dutta; Chin-Yu Huang (Cogent Economics & Finance, 2018)
We have investigated the influence of investors' expectation of future market trends on their trading and investment decisions in various market states. The efficiency of mutual-fund markets can be threatened by systematic biases in different decision-makings. Mutual-fund investors exhibit the disposition effect whereas neither type of investor exhibits such effect in the bear market. Stock-fund investors in the bull and neutral markets exhibit the disposition effect, whereas balanced-fund investors exhibit the disposition effect only in the neutral market. This study enables mutual-fund managers to plan cash holdings in the trading of various types of mutual funds and in various market states to respond to future fund investors' fund redemption. Multiple regression analysis is conducted to verify whether stock-fund investors are prone to exhibit the disposition effect in various market states. Stock-fund investors exhibit a higher tendency toward the disposition effect than the balanced-fund investors. In addition, in the bear market the redemption rate for the stock-fund investors is higher than that for the balanced-fund investors that resulted in a high turnover rate.
Keywords: 330; Disposition effect; stock and mutual-fund investors; bull and bear markets